TECHNICAL GUIDANCE OF GOAT WASTE TREATMENT IN IDAMAN LIVESTOCK GROUP, NORTH LANDASAN ULIN VILLAGE, BANJARBARU CITY - sugiarti sugiarti sugiarti (JURNAL PengaMAS, 2023)
Organic fertilizer is a complete fertilizer because it contains macro and micro elements even in small amounts. The use of natural organic fertilizers that can be used to help overcome agricultural production constraints is Liquid Organic Fertilizers. This organic fertilizer is processed from raw materials in the form of livestock manure, compost, natural waste, plant hormones and other natural ingredients. Liquid organic fertilizer can be created from goat manure (feces). Goat manure contains organic material that can provide nutrients for plants through the decomposition process. This process occurs gradually by releasing simple organic matter for plant growth. The Ideal Livestock Group is one of the fields in the Forest Farmers group located in the North Landasan Ulin Village, Banjarbaru City. The issues that exist are that goat manure has not been utilized so that there is a need for counseling about processing livestock manure and there is no refining of livestock waste that is manufactured into organic fertilizer. With these circumstances, the method offered to support the realization of community service programs for partners is to provide counseling about livestock waste processing and provide knowledge and skills as well as mastery of methods/techniques for processing livestock waste which is processed into fertilizer. The enthusiasm of the farmers to receive the recommendation that was carried out was reflected by a high response in the punctuality of attendance, the presence of participants in counseling activities and brainstorming with a percentage between 90-100%. Participants' insight of the material and implementation of the practice of making liquid fertilizer from livestock manure from the pre test showed that as many as 36.36% of farmers had understood and made liquid fertilizer and as many as 63.64% of farmers did not understand the manufacture of liquid fertilizer from goat manure. After the direction and the practice of making liquid fertilizer from goat manure, the farmers' understanding increased by 90.91% from the post test carried out. The liquid fertilizer produced is brown in color and smells sweet and sour. Liquid fertilizer can already be applied to plants and store fertilizer in plastic bottles. From this activity, it can be concluded that the Partners of the Ideal Livestock Group managed to understand well the manufacture of liquid fertilizer from goat manure and the participation rate of the participants was very good.Â Â Keyword: Organic fertilizer, Goat manure, Liquid organic, Farmers group